PEMBERIAN EDUKASI PADA INSIDENSI BALITA STUNTING DI WILAYAH KECAMATAN GUNUNG ANYAR KOTA SURABAYA - Wahyuni Dyah Parmasari; Emillia Devi Dwi Rianti; Indah Widyaningsih; Candra Rini Hasanah Putri (UNIVERSITAS PGRI MADIUN, 2025)
Abstract. The stunting case in Indonesia is a negative trend that must be eradicated. One of the causes of the incidence of stunting is due to a lack of nutritional intake before the mother becomes pregnant, during pregnancy, and after the child is born and grows. Toddlerhood is the golden period that determines the quality of a human's growth and development. This is one of the visions of the Indonesian government to eradicate malnutrition, especially during childhood. In Surabaya, the percentage of stunting still exists, although it is not significant. The community service was held in the Gunung Anyar work area, which is one of the marginal areas in Surabaya city planning. The purpose of this service is to provide education to cadres and mothers of stunted toddlers about the incident of stunted toddlers in the Gunung Anyar District, Surabaya City. The method of this service is to educate cadre mothers and mothers who have pre-stunting and stunting children. There are toddlers whose height is 90 cm at the age of 60 months (5 years) and 95 cm at the age of 48 months (4 years), this condition occurs in male toddlers. So toddlers 4 years old are already in ideal conditions, but toddlers 5 years old are not in ideal conditions. The incidence of stunted toddlers still exists, so it is a concern. The incidence of stunting is not large, but it must be a special concern, especially for the Surabaya city government, in alleviating the stunting problem to make the city of Surabaya zero stunting. Abstrak. Kasus stunting di Indonesia merupakan salah satu trend negatif yang harus dientaskan. Salah satu penyebab adanya Insidensi Stunting dikarenakan adanya kurangnya asupan nutrisi dari sebelum ibu hamil, selama masa kehamilan, dan setelah anak tersebut lahir dan tumbuh. Masa balita merupakan periode emas penentu kualitas tumbuh kembang seorang maniusia. Hal ini salah satu visi dari pemerintah Indonesia untuk mengentasan malnutrisi khususnya masa balita. Di Surabaya presentase stunting masih ada, walaupun tidak signifikan. Pengabdian masyarakat diadakan di wilayah kerja Gunung Anyar, yang merupakan salah satu wilayah marginal dalam tata kota Surabaya. Tujuan pengabdian ini adalah memberikan edukasi pada kader dan ibu balita stunting tentang insiden si balita stunting di wilayah Kecamatan Gunung Anyar, Kota Surabaya. Metode dari pengabdian ini dengan mengedukasi ibu-ibu kader dan para ibu yang memiliki anak pra-stunting dan stunting. terdapat balita yang memiliki tinggi badan 90 cm di usia 60 bulan (5 tahun) dan 95 cm diusia 48 bulan (4 tahun), kondisi tersebut terjadi pada balita laki-laki. Maka dengan balita yang berusia 4 tahun sudah masuk dalam kondisi ideal, akan tetapi utuk balita yang berusia 5 tahun masuk dalam kondisi tidak ideal. Insidensi balita stunting masih ada, sehingga menjadi perhatian. Insidensi Stunting didapat angkanya tidak besar tetapi harus menjadi perhatian khusus, khususnya pemerintah kota Surabaya dalam mengentaskan masalah stunting sehingga menjadikan Kota Surabaya yang Zero Stunting.